Prediction Of Disc Brake Contact Pressure Distributions By Finite Element Analysis - Abu Bakar, Abd Rahim; Huajiang, Ouyang (Penerbit UTM Press, 2005)
In Recent Years, Prediction Of Contact Pressure Distributions Is Regarded As An Important Step In Studying Disc Brake Squeal Noise. Contact Analysis Forms Part Of The Whole Procedure In The Complex Eigenvalue Method. The Essence Of Such A Method Lies In The Asymmetric Stiffness Matrix Derived From The Contact Stiffness And The Friction Coefficient At The Disc/Pads Interfaces. This Paper Presents The Analysis Of The Contact Pressure Distributions At The Disc/Pad Interfaces Using A Detailed 3-Dimensional Finite Element Model Of A Real Car Disc Brake. A General-Purpose Commercial Software Package Was Utilised And Assessed. The Paper Also Investigates Different Levels In Modeling A Disc Brake And Simulating Contact Pressure Distributions. Having Obtained The Suitable Model, Prediction Of Interface Pressure Distributions On An Original Disc Brake Was Carried Out. Finally, Modifications On The Geometry And/Or Materials Of Disc Brake Components Were Performed To Search For A More Uniform Contact Pressure Distribution. It Is Believed That A Uniform Contact Pressure Distribution Could Prevent Excessive Tapered Wear On The Pads And Subsequently Could Prolong The Life Of Pads.